ANALISIS DINAMIK RESPONS SPEKTRUM DAN STATIK EKUIVALEN GEDUNG PERKULIAHAN UNIVERSITAS SEMARANG - Talitha Zhafira; Imawan Taufiqy; Purwanto; Mustain; Nurti Kusuma Anggraini (Universitas Medan Area, 2023)
In the planning building structures, the calculation lateral loads due to earthquakes is very necessary. Spectrum response analysis is a way of analyzing the relationship between the period of a building structure and the value the building's acceleration when an earthquake hits it. Equivalent static analysis is usually used in buildings that are not too high, where the load effect on the structure is considered a horizontal static load due to ground movement. This study uses the lecture building object at the University of Semarang with the dynamic response spectrum and static equivalent methods. This study aims to determine the level of building safety due to earthquake loads according to SNI for earthquake resistance planning 1726; 2019 with base shear, displacement, story drift, and P-delta effects using the ETABS V.18.02. The results of analysis, the Semarang University lecture building stated that it was safe with a dynamic base shear spectrum response of not less than 100% static earthquake, maximum displacement with a value of 44 mm, the story drift value of all floors was still below the limit of 46.154 mm, so the structure of the lecture building was still in the safe category against working load. The effect of p-delta in this study is ignored because the boundary coefficient for each floor is less than 0.10.